Comparative study of fast pyrolysis, hydropyrolysis and catalytic hydropyrolysis of poplar sawdust and rice husk in a modified Py-GC/MS microreactor system: Insights into product distribution, quantum description and reaction mechanism. (March 2020) - He, Yifeng; Zhao, Yingnan; Chai, Meiyun; Zhou, Zhongyue; Sarker, Manobendro; Li, Chong; Liu, Ronghou; Cai, Junmeng; Liu, Xinghua
Abstract: Fast pyrolysis, hydropyrolysis and catalytic hydropyrolysis are three important methods to produce bio-oil from biomass and are of great interest to researchers. In this research, the comprehensive study of pyrolysis, hydropyrolysis and catalytic hydropyrolysis of poplar sawdust and rice husk was investigated in a modified laboratory Py-GC/MS microreactor system. Rh/ZrO2 (0.5 wt %) was prepared and applied in the catalytic hydropyrolysis process. An evaluation system including estimating method of product selectivity, the calculation method of O/C and H/C ratio, deoxygenation extent (DE) and hydrogen-loss extent (HLE), was established to fully measure the deoxygenation effect. The Rh/ZrO2 -assisted catalytic hydropyrolysis showed a good deoxygenation effect as O/C ratios (0.10 for poplar sawdust, 0.11 for rice husk, respectively) are comparable to that of the reported upgraded bio-oil by hydrodeoxygenation (HDO). The highest hydrocarbon selectivity of 49.14% and DE of 87.6% were obtained in catalytic hydropyrolysis of poplar sawdust. For rice husk, the hydropyrolysis process gained a similar DE (82.7%) to that of the catalytic HyPy (83.7%), because rice husk with high ash content (19.4 wt %) contains a large number of mineral elements that are likely to form a self-catalysis effect. The reaction mechanism was further inferred according to product distribution and quantum calculation of oxygen-containing products, suggesting that Rh/ZrO2 -assisted hydropyrolysis was accomplished by multistage reactions, involving initial pyrolysis of raw biomass and further deoxygenation of the pyrolysis intermediates. Moreover, this work can also provide a proven methodology and theoretical supports for future studies on catalytic hydropyrolysis of biomass. Graphical abstract: Image 1 Highlights: A comprehensive study of Py, HyPy and catalytic HyPy of poplar sawdust and rice husk was reported. Rh/ZrO2 -assisted HyPy of poplar sawdust obtained the most hydrocarbons (49.14%) and DE (87.6%). Similar DE was obtained in HyPy and catalytic HyPy of rice husk. Quantum descriptors calculation provides theoretical support for mechanism study.